Sub‐types of insomnia in adolescents: Insights from a quantitative/molecular twin study - Juan J. Madrid‐Valero; Frühling Rijsdijk; Saskia Selzam; Helena M. S. Zavos; Melanie Schneider; Angelica Ronald; Alice M. Gregory (Wiley, 2023)
Abstract Background Insomnia with short sleep duration has been postulated as more severe than that accompanied by normal/long sleep length. While the short duration subtype is considered to have greater genetic influence than the other subtype, no studies have addressed this question. This study aimed to compare these subtypes in terms of: (1) the heritability of insomnia symptoms; (2) polygenic scores (PGS) for insomnia symptoms and sleep duration; (3) the associations between insomnia symptoms and a wide variety of traits/disorders. Methods The sample comprised 4000 pairs of twins aged 16 from the Twins Early Development Study. Twin models were fitted to estimate the heritability of insomnia in both groups. PGS were calculated for self‐reported insomnia and sleep duration and compared among participants with short and normal/long sleep duration. Results Heritability was not significantly different in the short sleep duration group (A = 0.13 [95%CI = 0.01, 0.32]) and the normal/long sleep duration group (A = 0.35 [95%CI = 0.29, 0.40]). Shared environmental factors accounted for a substantial proportion of the variance in the short sleep duration group (C = 0.19 [95%CI = 0.05, 0.32]) but not in the normal/long sleep duration group (C = 0.00 [95%CI = 0.00, 0.04]). PGS did not differ significantly between groups although results were in the direction expected by the theory. Our results also showed that insomnia with short (as compared to normal/long) sleep duration had a stronger association with anxiety and depression (p < .05)-although not once adjusting for multiple testing. Conclusions We found mixed results in relation to the expected differences between the insomnia subtypes in adolescents. Future research needs to further establish cut‐offs for 'short' sleep at different developmental stages and employ objective measures of sleep.